2015
DOI: 10.1016/j.shpsc.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Can biological complexity be reverse engineered?

Abstract: Concerns with the use of engineering approaches in biology have recently been raised. I examine two related challenges to biological research that I call the synchronic and diachronic underdetermination problem. The former refers to challenges associated with the inference of design principles underlying system capacities when the synchronic relations between lowerlevel processes and higher-level systems capacities are degenerate (many-to-many). The diachronic underdetermination problem regards the problem of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…However, it is debated whether methodological reduction can lead to oversimplified ontological accounts of living systems (cf. Green 2015;Nicholson 2013). In spite of their success in 20th Century biology, it has been argued that reductionist strategies are inherently limited and lead to partial or incomplete accounts of living phenomena, either because some organizational features of biological systems are irreducible to the lower level (e.g.…”
Section: Reductionism and Its Limits In Molecular Biologymentioning
confidence: 99%
“…However, it is debated whether methodological reduction can lead to oversimplified ontological accounts of living systems (cf. Green 2015;Nicholson 2013). In spite of their success in 20th Century biology, it has been argued that reductionist strategies are inherently limited and lead to partial or incomplete accounts of living phenomena, either because some organizational features of biological systems are irreducible to the lower level (e.g.…”
Section: Reductionism and Its Limits In Molecular Biologymentioning
confidence: 99%
“…The epigenetic landscape serves as conceptual framework with the potential to integrate mathematical modelling based on dynamical systems theory and experimental manipulation of cell development (Fagan, ). In this context, theoretical approaches can benefit from experimental resources that give their abstract models empirical (or biological) grounding, while dynamical systems theory in time may allow for prediction of developmental trajectories based on quantitative modelling (Green, , ).…”
Section: Reduction Imperialism and Suggestions For Practical Integrmentioning
confidence: 99%
“…However, given that there are concepts, principles, and laws governing the types of solutions that nature can arrive at, these principles and laws are discoverable. Science enables us to learn from nature, and we know that once we have understood the principles and laws behind natural designs and design evolution, we can apply these lessons effectively, for example as already accomplished in fields such as biomimicry (Benyus, ; Green, ). We have also shown that we can apply these lessons in ways that improve on the efficiency of nature's methods and processes.…”
Section: Elegant Complexity In Naturementioning
confidence: 99%